Significance of Serological Markers in Diagnosis of Acute Dengue Infection: 2021 Outbreak - Saifullah Khan Niazi; Aymen Bibi; Eijaz Ghani; Muhammad Ali Rathore; Hammad Hussain; Hina Hammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To highlight the significance of Dengue anti-IgM and Dengue NS1 antigen in diagnosing Acute Dengue infection.